BCAS2 interacts with HSF4 and negatively regulates its protein stability via ubiquitination. (November 2015) - Liao, Shengjie; Du, Rong; Wang, Lei; Qu, Zhen; Cui, Xiukun; Li, Chang; Liu, Fei; Huang, Mi; Wang, Jiuxiang; Chen, Jiaxiang; Gao, Meng; Yu, Shanshan; et al.
Highlights: BCAS2 is a novel interacting partner of HSF4. BCAS2 negatively regulates HSF4 protein stability and its target gene expression. BCAS2 mediated HSF4 degradation through ubiquitination. The K206 residue of HSF4 is essential for its ubiquitination. Abstract: Heat shock factor 4 (HSF4) is an important transcriptional factor that plays a vital role in lens development and differentiation, but the mechanism underlying the regulation of HSF4 is ambiguous. BCAS2 was reported to be an essential subunit of pre-mRNA splicing complex. Here, we identified BCAS2 as a novel HSF4 interacting partner. High expression of BCAS2 in the lens epithelium cells and the bow region of mouse lens was detected by immunohistochemistry. In human lens epithelial cells, BCAS2 negatively regulates HSF4 protein level and transcriptional activity, whereas in BCAS2 knockdown cells, HSF4 protein stability was increased significantly. We further demonstrated that the prolonged protein half-time of HSF4 in BCAS2 knockdown cells was due to reduced ubiquitination. Moreover, we have identified the lysine 206 of HSF4 as the key residue for ubiquitination. The HSF4-K206R mutant blocked the impact of BCAS2 on HSF4 protein stability. Taken together, we identified a pathway for HSF4 degradation through the ubiquitin–proteasome system, and a novel function for BCAS2 that may act as a negative regulatory factor for modulating HSF4 protein homeostasis.